2015
DOI: 10.1007/s00423-015-1331-x
|View full text |Cite
|
Sign up to set email alerts
|

Hand-assisted hybrid laparoscopic–robotic total proctocolectomy with ileal pouch–anal anastomosis

Abstract: The hand-assisted hybrid laparoscopic-robotic approach to total proctocolectomy with IPAA has not been previously described. Our report shows the feasibility of this hybrid approach, which surpasses most of the limitations of pure laparoscopic and robotic techniques. Further experience is necessary to refine the technique and fully assess its potential advantages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…2010 17 Control = 17 13:UC, 2: IC 2:Crohn’s CMOR 4 10 lap. assisted (for mobilisation of distal ileal mesentery and division of superior haemorrhoidal artery) robotic proctectomy with extracorporeal formation of J-pouch through Pfannenstiel incision with formation of an IPAA through an open approach using a double-stapled technique, and loop ileostomy 7 laparoscopic-assisted (for division of superior haemorrhoidal artery) robotic completion proctectomy (CP) Control: Laparoscopic proctectomy Note all patients had previously undergone laparoscopic colectomy 3 robotic arms (RLQ and LLQ, 12 mm camera at umbilicus), assistant port at ostomy site, assistant port LUQ NR RP-CP: 90 ± 29.9 RP–IPAA: 86 ± 16.5 RP-CP: 351 ± 76.3 (compared to LP-CP p = 0.03) RP–IPAA: 370 ± 65.9 (compared to LP–IPAA p = 0.14) Morelli et al [ 20 ] Pisa, Italy 2015 Feb. 2010–March 2014 1 UC CR 3 Robotic proctectomy following hand-assisted laparoscopic colectomy and subsequent extracorporeal formation of J-pouch, with hand-sewn IPAA via a perineal approach, and loop ileostomy 4 robotic arms Single 99 238 Pedraza et al [ 21 ] Tx, USA 2011 Aug. 2008–Feb. 2010 5 UC CS 4 Robotic proctectomy following laparoscopic colectomy and subsequent extracorporeal formation of J-pouch and formation of IPAA under robotic vision, and loop ileostomy 4 robotic arms (12 mm camera at umbilicus, 8 mm RLQ, 8 mm LLQ, 8 mm L loin), 12 mm assistant port site R loin Single 138.8 ± 35.0 330 ± 47.4 Rencuzogullari et al [ 22 ] Cleveland, Ohio, USA 2016 Jan. 2010–June 2014 21 Control = 21 17 UC 4 Crohn’s CMOR 2 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…2010 17 Control = 17 13:UC, 2: IC 2:Crohn’s CMOR 4 10 lap. assisted (for mobilisation of distal ileal mesentery and division of superior haemorrhoidal artery) robotic proctectomy with extracorporeal formation of J-pouch through Pfannenstiel incision with formation of an IPAA through an open approach using a double-stapled technique, and loop ileostomy 7 laparoscopic-assisted (for division of superior haemorrhoidal artery) robotic completion proctectomy (CP) Control: Laparoscopic proctectomy Note all patients had previously undergone laparoscopic colectomy 3 robotic arms (RLQ and LLQ, 12 mm camera at umbilicus), assistant port at ostomy site, assistant port LUQ NR RP-CP: 90 ± 29.9 RP–IPAA: 86 ± 16.5 RP-CP: 351 ± 76.3 (compared to LP-CP p = 0.03) RP–IPAA: 370 ± 65.9 (compared to LP–IPAA p = 0.14) Morelli et al [ 20 ] Pisa, Italy 2015 Feb. 2010–March 2014 1 UC CR 3 Robotic proctectomy following hand-assisted laparoscopic colectomy and subsequent extracorporeal formation of J-pouch, with hand-sewn IPAA via a perineal approach, and loop ileostomy 4 robotic arms Single 99 238 Pedraza et al [ 21 ] Tx, USA 2011 Aug. 2008–Feb. 2010 5 UC CS 4 Robotic proctectomy following laparoscopic colectomy and subsequent extracorporeal formation of J-pouch and formation of IPAA under robotic vision, and loop ileostomy 4 robotic arms (12 mm camera at umbilicus, 8 mm RLQ, 8 mm LLQ, 8 mm L loin), 12 mm assistant port site R loin Single 138.8 ± 35.0 330 ± 47.4 Rencuzogullari et al [ 22 ] Cleveland, Ohio, USA 2016 Jan. 2010–June 2014 21 Control = 21 17 UC 4 Crohn’s CMOR 2 …”
Section: Resultsmentioning
confidence: 99%
“…100% of the high-risk patients operated on with fulminant UC by McLemore et al [ 18 ] experienced early complications, although all complications were a maximum of Clavien-Dindo II. The single case report did not describe any complications [ 20 ]. The remaining studies reported a morbidity rate of 40–75%.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations